2012
DOI: 10.1371/journal.pone.0040011
|View full text |Cite
|
Sign up to set email alerts
|

SFTA2—A Novel Secretory Peptide Highly Expressed in the Lung—Is Modulated by Lipopolysaccharide but Not Hyperoxia

Abstract: Tissue-specific transcripts are likely to be of importance for the corresponding organ. While attempting to define the specific transcriptome of the human lung, we identified the transcript of a yet uncharacterized protein, SFTA2. In silico analyses, biochemical methods, fluorescence imaging and animal challenge experiments were employed to characterize SFTA2. Human SFTA2 is located on Chr. 6p21.33, a disease-susceptibility locus for diffuse panbronchiolitis. RT-PCR verified the abundance of SFTA2-specific tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 26 publications
3
24
1
Order By: Relevance
“…For testing the antibodies, we performed Western blot analysis using human lung tissue, because all known surfactant proteins were identified and characterized also in the lung [1], [2], [13], [64], [65]. Furthermore, a very recent study of Mittal et al also demonstrated the presence of SP-G within lung tissue [66]. The corresponding Western blot analysis show specific bands at 11 kDa, 20 kDa and 30 kDa.…”
Section: Discussionmentioning
confidence: 99%
“…For testing the antibodies, we performed Western blot analysis using human lung tissue, because all known surfactant proteins were identified and characterized also in the lung [1], [2], [13], [64], [65]. Furthermore, a very recent study of Mittal et al also demonstrated the presence of SP-G within lung tissue [66]. The corresponding Western blot analysis show specific bands at 11 kDa, 20 kDa and 30 kDa.…”
Section: Discussionmentioning
confidence: 99%
“…28 Remarkably, three small prolinerich protein encoding genes (SPRR1A, SPRR1B, and SPRR3) and four surfactant or surfactant-associated protein encoding genes (SFTPA2, SFTPB, SFTA2, and SFTA3) were also on our selected list, in accordance with the former trio being highly expressed in squamous epithelial cells and carcinomas, 29 and the latter being characteristic for secretory alveolar cells and ACs. [30][31][32] Another gene from our list, DSG3, encodes for desmoglein 3, a component of the intercellular desmosomal junction, which is highly upregulated in squamous cell carcinoma of the lung, compared with AC, and has been suggested as a good marker of the former. 33,34 The strengths of our approach reside in the fact that it proved to be reliable on several data sets with relatively minimal user interaction in the process and tuning from one data set to the other.…”
Section: Copdmentioning
confidence: 99%
“…SFTA2 orthologs are present in all mammals. In a mouse model, Sfta2 was strongly down‐regulated after intratracheal injections of lipopolysaccharides ; it was also found to be implicated in lung function development . SFTA2 SNPs were associated with four of six PF phenotypes under study available through the Global Biobank Engine.…”
Section: Discussionmentioning
confidence: 98%
“…SFTA2 (SP‐G) protein is highly expressed in lung; namely, in alveolar type II and in non‐ciliated bronchiolar cells. It is expressed in parallel with hydrophobic surfactant proteins B and C, and has physicochemical properties similar to those known for these surfactants . SFTA2 orthologs are present in all mammals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation